Insufficient sleep in young athletes? Causes, consequences, and potential treatments - Fox, J. L.; Scanlan, A. T.; Stanton, R.; Sargent, C. (Sports Medicine, 2019)
Sleep is essential in the preparation for, and the recovery from, training and competition. Despite being important for all indi-viduals, young athletes are considered an at-risk group for reduced sleep duration and quality. The purpose of this review is to synthesise current literature relating to sleep duration and quality in young (14-25 years) athletes. Specifically, typical sleep and wake patterns, factors affecting sleep and wake patterns, and the consequences of altered sleep and wake patterns in young ath-letes are discussed. Scheduling training and competition in the afternoon or evening appears to result in reduced sleep duration due to less time in bed. Evidence suggests that young athletes who obtain less than 8 h of sleep per night are at a higher risk of musculoskeletal injury. An increase in sleep duration above habitual nightly sleep may be associated with favourable performance in young athletes; however, the associations between sleep quality and performance- and health-related outcomes remain unclear.